Ocupação do distrito de Aracê, Domingo Martins (1888-1920). - Batista, Márcia Regina (2019)
The Aracê district, county of Domingos Martins, Espírito Santo, was occuped in the ending of XIX century and the beggining of XX century, by national and foreign immigrants who found in the area, at the time of their arrival, indigenous people of the Puris tribe.This occupation was made by heterogeneous groups, but a strong appeal to european colonization highlighted the coming of german immigrants and mainly italians and deprecated the nationals presence. The forming elements of the local people were: indigenous people; national immigrants, like native from Rio de Janeiro (fluminenses), Ceará and Minas Gerais; foreign immigrants and their descendants, especially germans and italians, and people from Espírito Santo. Also stand out the multiple ways used for the formation of Aracê district. The time frame of this dissertation begins in the year 1888, when possibly arrived the first region´s residents, and it ends at the year 1920, when the agricultural census already points the presence of all of the considered families by the community as the district´s founders. Was resorted to Microstorie (LEVI, 1998) to reconstruct the locality´s history and understand in a closer way its peculiarities. The fundamental element for the past´s reconstruction of this area was made by interviews with its residents, which methodology provided informations that led to the documentary sources that, added together, allowed to stabilish the origin and the path of the first families. The use of regards is justified (BOSI; 1999) because the memorie is not just personal, but also retreats a society in determinated period of time. It was applied to the found documents a meticulous analisys of details (GINZBURG, 1989) to rescue informations that would allow to set up the history of the Aracê district´s past. During the writing process of this dissertation, the interviews with the comunity provided clues and evidences to find documentary evidences. However, when analyzing the 1920´s Census of Rural Establishments, the process has reversed: the document could count with the comunity to cover your gaps. Then, this dissertation is the result of circular search between obtained informations in comunity which lead us to documents and the document analysis that brought us back to the comunity. The result of this research was the reconstruction of Aracê district ocupation and the rescue of the ways to this ocupation, looking to evidence that multiple ethnicities participated in the formation of the locality and refute, thereby, the idea that it has been predominantly ocupated by european immigrants.